Comparative eye and liver differentially expressed genes reveal monochromatic vision and cancer resistance in the shortfin mako shark (Isurus oxyrinchus) - Domingues, Rodrigo R.; Mastrochirico-Filho, Vito Antonio [UNESP]; Mendes, Natalia J. [UNESP]; Hashimoto, Diogo T. [UNESP]; Coelho, Rui; da Cruz, Vanessa Paes [UNESP]; Antunes, Agostinho; Foresti, Fausto [UNESP]; Mendonça, Fernando F. (Elsevier, 2020)
The shortfin mako, Isurus oxyrinchus is an oceanic pelagic shark found worldwide in tropical and subtropical waters. However, the understanding of its biology at molecular level is still incipient. We sequenced the messenger RNA isolated from eye and liver tissues. De novo transcriptome yielded a total of 705,940 transcripts. A total of 3774 genes were differentially expressed (DEGs), with 1612 in the eye and 2162 in the liver. Most DEGs in the eye were related to structural and signaling functions, including nonocular and ocular opsin genes, whereas nine out of ten most overexpressed genes in the liver were related to tumor suppression, wound healing, and human diseases. Furthermore, DEGs findings provide insights on the monochromatic shark vision and a repertory of cancer-related genes, which may be insightful to elucidate shark resistance to cancer. Therefore, our results provide valuable sequence resources for future functional and population studies.
Keywords: Elasmobranch; Gene ontology; Photoreception; Transcriptomics; Tumor suppression